2009 IEEE/AIAA 28th Digital Avionics Systems Conference 2009
DOI: 10.1109/dasc.2009.5347571
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of wake vortex models and sensors in modern avionic systems

Abstract: Today's airport capacity is severely limited by separation of approaching and to a lesser extent departing aircraft to ensure that following aircraft do not encounter the wake vortex generated by the preceding one. The encounter of wake vortices, especially during take-off and landing, can cause critical or even catastrophic flight situations for the succeeding plane. Historically, the wake vortex separation standards are based on a 'worst-casescenario' assuming calm and still air conditions responsible for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…During the measurement update in Eq. (7), the pendant to the LIDAR measurements need to be calculated from the system state. While the wake vortex strength is directly estimated in the system state, the position needs to be transferred into the measurement coordinate system of the LIDAR.…”
Section: A Ekf Layoutmentioning
confidence: 99%
“…During the measurement update in Eq. (7), the pendant to the LIDAR measurements need to be calculated from the system state. While the wake vortex strength is directly estimated in the system state, the position needs to be transferred into the measurement coordinate system of the LIDAR.…”
Section: A Ekf Layoutmentioning
confidence: 99%
“…An additional goal of the simulation environment is to find the minimum operational performance for the lidar sensor that is needed to achieve the target of monitoring the own-ship wake-vortex decay. To reach this goal, the system itself is composed of a wake-vortex prediction algorithm and an integrated fusion filter that combines the wakevortex prediction and the lidar measurement in a similar way as described in [6]. The simulation framework will allow an investigation on how parameters of wing geometry can describe, for example, the influence of flap settings within the wake-vortex transport and decay prediction.…”
Section: B Validation Of the Wake-vortex Module Of The Software Frammentioning
confidence: 99%
“…Recently conducted studies (e.g., Boeing, see [5]) have shown that the use of active flaps could be beneficial for a faster decay of wake vortices, presuming that meteorological influences on wake decay are weak. Combined with the knowledge of the atmosphere behind the aircraft (which the aircraft has just passed), a prediction about the decay behind the aircraft based on numeric models (see for example [6]) will be possible. The Institute of Flight Guidance of the Technische Universität Braunschweig (TUBS-IFF) is working on a simulation environment where the own-ship vortices will be modeled, combined with a backward-looking onboard lidar installation.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement matrix H is used to relate the vector of measured error z and the filter state vector to each other according to equation (16), where the superscript þ means a posteriori state, i.e. after correction by measurement updatê…”
Section: Implementation Of a Closed-loop Error-state Systemmentioning
confidence: 99%
“…The approach described above aims at providing more accurate information on the wake vortex state than the sole prediction or only sensor measurements. In order to investigate this ability, simulations were used 16 where intentionally erroneous meteorological information was provided to the model. The crosswind that is an essential mechanism for lateral wake transport was charged with a constant offset up to the normalized time t à ¼ 4.…”
Section: Implementation Of a Closed-loop Error-state Systemmentioning
confidence: 99%